Antifungal activity of fermentates and their potential to replace propionate in bread. (March 2017) - Samapundo, Simbarashe; Devlieghere, Frank; Vroman, Annemarie; Eeckhout, Mia
Abstract: The major objective of this study was to assess the potential of commercially available 'clean label' fermentates to replace the preservative function of propionate in bread. This study was performed in two parts. In the first part of the study the inhibitory activities of selected fermentates, FA (cultured corn syrup and citric acid), FB (cultured wheat solids), FC (cultured dextrose) and FD (cultured dextrose), towards Penicillium chrysogenum and Penicillium paneum were assessed as a function of pH (4.5–6.5) on malt extract agar (MEA). In the second part of the study, challenge, shelf-life and sensorial tests were used to determine the suitability of these fermentates to replace calcium propionate in bread. All the fermentates evaluated in this study had appreciable inhibitory activities towards P. chrysogenum and P. paneum . As expected the antifungal activity of the fermentates was greater the lower the pH of the growth medium. Additionally, P. paneum was generally more tolerant to the fermentates than P. chrysogenum . The challenge and sensorial tests showed that bread prepared with FA (1.3%), FB (2%) and FC (1.3 and 2%) were as microbiologically stable and sensorially acceptable as the reference. Therefore, fermentates can be used as 'label friendly' preservatives in bread products. Highlights: Antifungal activity of selected commercial fermentates was evaluated. All fermentates had significant inhibitory activities towards Penicillium spp. Antifungal activity of the fermentates was pH and isolate dependent. Fermentates FA, FB and FC can be used to replace propionate in bread.